Impairment of entorhinal cortex network activity in Alzheimer’s disease - Karimani, Farnaz; Asgari Taei, Afsaneh; Abolghasemi-Dehaghani, Mohammad-Reza; Safari, Mir-Shahram; Dargahi, Leila (Frontiers in Aging Neuroscience, 2024)
The entorhinal cortex (EC) stands out as a critical brain region affected in the early phases of Alzheimer’s disease (AD), with some of the disease’s pathological processes originating from this area, making it one of the most crucial brain regions in AD. Recent research highlights disruptions in the brain’s network activity, characterized by heightened excitability and irregular oscillations, may contribute to cognitive impairment. These disruptions are proposed not only as potential therapeutic targets but also as early biomarkers for AD. In this paper, we will begin with a review of the anatomy and function of EC, highlighting its selective vulnerability in AD. Subsequently, we will discuss the disruption of EC network activity, exploring changes in excitability and neuronal oscillations in this region during AD and hypothesize that, considering the advancements in neuromodulation techniques, addressing the disturbances in the network activity of the EC could offer fresh insights for both the diagnosis and treatment of AD.